PENINGKATAN HASIL BELAJAR PANGKAT RASIONAL DAN BENTUK AKAR MENGGUNAKAN MEDIA LEMBAR SIMULASI - Sri Wahyuni (Universitas Sarjanawiyata Tamansiswa, 2016)
Sheet simulation is a media that can improve student learning outcomes, increasing the active response of students, and relieve tension and tired of learning mathematics. Media is in accordance with the character of the student and student interests and habits of students. The learning process with this medium is a model of the games and discussions group involving a student with a jovial mood, learning and thinking.